Assessment of the existing models to evaluate the shear strength contribution of externally bonded frp shear reinforcements. (15th June 2021) - Oller, Eva; Kotynia, Renata; Marí, Antonio
Abstract: This paper presents an analysis of the performance of different existing formulations to quantify the FRP contribution to the shear strength of RC elements strengthened in shear by externally bonded FRP sheets. A large database of 555 tests has been assembled distinguishing between the shape of the section, the existence of internal transverse reinforcement and the FRP configurations. In general, predictions are more conservative for beams without transverse reinforcement. In addition, in some cases predictions are unsafe for beams with transverse reinforcement, showing a possible interaction with the internal transverse reinforcement which is not considered in the experimental FRP contribution to the shear strength. For wrapped FRP configurations, models generally assumed failure at the bottom corner of the section and results are very conservative in some cases where failure was experimentally observed along the web. For U-shaped and side-bonded configuration, results depend mainly on the assumed bond model and are more accurate than in the previous case, showing for some models unsafe predictions for the continuous FRP system applied in beams with transverse reinforcement.